Strategi Implementasi Kurikulum 2013 di Era Disrupsi - Fitriatun Nazila (FONDATIA, 2019)
This research is based on the study of literature which contains the strategy for implementing the 2013 curriculum in the era of disruption. This study aims to examine the strategy of implementing the 2013 curriculum in order to deal with the demands of the development of the era which almost all involve information technology. The design of this study is qualitative using the library research method. The technical data analysis used is content analysis. Curriculum 2013 as a perfect curriculum from several previous curriculums based on the development of children's character with a systematic and efficient learning process is seen as able to deal with and bridge this disruption era because the development of the 2013 curriculum not only changes the content of previous learning material (not urgency) but also demand universal understanding of students and be able to contribute to the development of student skills so that they make humans who can play an active role in advancing the nation. However, this is inseparable from the role of educators as facilitators in delivering curriculum content material and must play an active role in developing more innovative teaching materials and learning methods to achieve educational goals, namely to educate and mature the nation's children.